(untitled) (The Journal of Nuwakot Adarsha Multiple Campus, 2024)
Nepal’s strategic location between India and China defines its geopolitical significance and impacts its national security. This study examines how Nepal’s geographic position influences its security policies and international relations, emphasizing its historical efforts to balance ties with neighbors while safeguarding sovereignty, based on the review of existing literature on geopolitics and national security, particularly focusing on Nepal-India-China relations. Despite its neutral stance in international conflict between or among the countries, Nepal faces increasing internal security challenges amid shifting regional and global dynamics. The research identifies Nepal’s location as crucial to its security, particularly in energy, water resource management, trade, and in the region. While traditionally maintaining a balance between India and China, Nepal now encounters heightened external competition and internal instability, creating both strategic opportunities and vulnerabilities at a same time. Adapting its national security strategy to address these challenges, it is essential to take care of including managing trade routes, border control, and resource cooperation. The study concludes that Nepal must navigate the evolving geopolitical landscape by leveraging economic and diplomatic opportunities while addressing internal challenges like political instability and internal security. A balanced approach to diplomacy, security, and development will be vital for ensuring resilience and stability in an increasingly competitive region.